RECREATIONAL TECHNOLOGY IN PEDIATRIC AND SURGICAL UNITS: PRODUCTION BASED ON SCIENTIFIC EVIDENCE: Recreational technology for the hospitalized child - Valentim da Silva Moreira , Italo; da Silva Sabino, Aderlaine; Andrade da cunha Marques, Anne Grace; Véras Fontes Esteves , Arinete (Journal of Health Care, 2023)
Introduction: each and every child, wherever he/she is, has the right to play. Nonetheless, when a child is ill, he/she may undergo treatment with hospital admissions and actions that affect his/her routine, taking him/her away from his/her peers and possibly depriving him/her of playing. This situation implies little social contact with other children, emotional difficulties, and a low level of physical activity, which can entail losses to the child. Objective: to analyze the scientific evidence on the importance and benefits of recreational technologies used in pediatric surgical units. Materials and Methods: integrative review study, with a research question developed through the PICO strategy, selecting the descriptors "Biomedical Technology", "Recreation", "Surgicenter", "Operating Room", "Surgical Block", "Surgery", "Operating Room", "Pediatric Nursing", "Nursing Team", "Nursing Professionals", "Nurses" and "Child Health", in Portuguese and English, and using the Boolean operator AND or OR. The search was held in four sources of scientific literature, during the period from September 2020 to February 2021. The inclusion and exclusion criteria were applied, and the data were extracted using the form itself. Results: the final sample quantified twelve studies and their results were grouped into two categories: Playful activities and their benefits for the hospitalized child; Perception of professionals and family members concerning patient recreation. Conclusion: the study will help health professionals to achieve a different look at the care of hospitalized patients, taking into account that playing offers essential subsidies in terms of alleviating distress.